2014
DOI: 10.1002/ajh.23648
|View full text |Cite
|
Sign up to set email alerts
|

Auer‐rod like inclusions in multiple myeloma

Abstract: A variety of types of inclusions are seen in the neoplastic cells of multiple myeloma (plasma cell myeloma). Among these, crystalline inclusions resembling Auer rods are uncommon. This 47-year-old Iraqi woman presented with back pain and anemia (haemoglobin concentration 100 g/l). A diagnosis of immunoglobulin (Ig) Gj myeloma with Bence-Jones proteinuria was made [1]. The bone marrow was heavily infiltrated by cytologically abnormal plasma cells including multinucleated and nucleolated cells (left). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The cells stained positive by EST in four of nine cases and none were positive in MPO or PAS staining. There are other reports, which demonstrated that Auer rod-like inclusions were detected in cytoplasm of myeloma cells [25][26][27][28][29][30][31]. We considered that the inclusions in the cells of the GM group were not identifiable with Auer-like rods, because the shape of inclusions in the GM cells was quite different from that of Auer-like rods.…”
Section: Discussionmentioning
confidence: 97%
“…The cells stained positive by EST in four of nine cases and none were positive in MPO or PAS staining. There are other reports, which demonstrated that Auer rod-like inclusions were detected in cytoplasm of myeloma cells [25][26][27][28][29][30][31]. We considered that the inclusions in the cells of the GM group were not identifiable with Auer-like rods, because the shape of inclusions in the GM cells was quite different from that of Auer-like rods.…”
Section: Discussionmentioning
confidence: 97%
“…Steinmann was also the first time to prove that these inclusions to be of lysosomal origin (fusionated lysosomal granules). Following that report, many more cases have been described [1,2,[4][5][6][7][8][9][10]. Pooling together all the cases reviewed by Hütter [1] and other reports, including our cases, it appears that this phenomenon is always associated with a IgG κ-type paraprotein, only two cases of λ light chain restriction [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Pooling together all the cases reviewed by Hütter [1] and other reports, including our cases, it appears that this phenomenon is always associated with a IgG κ-type paraprotein, only two cases of λ light chain restriction [4][5][6][7][8][9][10][11][12][13][14]. Although plasma cell myeloma with these inclusion bodies has been considered to be a morphologic variant and has intrigued investigators, the prognostic value is still unclear [9][10][11][12][13][14]. Additionally, there is still no known cytogenetic association nor any particular immunophenotypic characteristic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In this patient with immunoglobulin G kappa myeloma a large proportion of the myeloma cells contained azurophilic granules, sometimes round and sometimes irregular (image). By analogy with the azurophilic Auer rod‐like inclusions with similar staining characteristics that may be observed in myeloma , it is likely that these inclusions are of lysosomal origin. In one reported case, the granules were positive for acid phosphatase and weakly positive for alpha naphthyl butyrate esterase; on ultrastructural examination they were distinct from the endoplasmic reticulum and were considered likely to be vacuoles of the lysosomal system .…”
mentioning
confidence: 87%